Bone health in older adults with an intellectual disability - Burke, Éilish (Trinity College (Dublin, Ireland). School of Nursing & Midwifery, 2016)
Intellectual disability (ID) is characterised by significant limitations of both adaptive behaviour and intellectual functioning. It is a prescribed term to describe a common understanding of what is being discussed or studied and it is not for the purposes of labelling or describing people. Currently the life expectancy of people with ID is increasing. However, the Health Service Executive (USE 2005) cautions that an increased older population could give rise to a significant increase in chronic diseases, one of which is osteoporosis. It has been reported that people with ID are two and half times more likely to present with adverse health conditions than the general population. Osteoporosis is strongly associated with ageing and as the older population of people with ID increase so too does their susceptibility to osteoporosis. Osteoporosis is a systematic skeletal disease characterised by microarchitectural deterioration of the bone with consequent increased vulnerability to fragility fracture. As an insidious condition it is very often only diagnosed post first clinical fracture
Keywords: Nursing and Midwifery Studies, Ph.D.; PhD Trinity College Dublin, 2016